Efficient authentication approach for highly dynamic vehicular ad hoc networks. (2015) - Grover, Kanika; Lim, Alvin; Lee, Seungbae
Vehicular ad hoc networks (VANETs) possess an extremely dynamic nature accompanying the high mobility feature. In VANETs, each vehicle sends out safety messages at regular intervals. IEEE 1609.2 security standard for VANETs recommend the use of secure elliptic curve digital signature algorithm (ECDSA) signatures for authenticating broadcast messages. ECDSA provides source authentication, message integrity and non-repudiation; with the drawback of signature verification overhead. Due to this, a large number of messages expire in the verification queue. Considering time-bound VANET broadcast messages authenticated using complex ECDSA verification, we propose a probabilistic verification for highly dynamic and mobile vehicles to reduce packet loss ratio. Along with our intelligent authentication strategy, we maintain conditional privacy of the vehicles through a lightweight vehicle registration process. We implement the complete solution in a realistic VANET scenario. With ns-2 simulations, we show that our algorithm decreases message loss by an overall average of 68% compared to other broadcast authentication algorithms.